The arc-scale spatial distribution of volcano erosion implies coupled magmatism and regional climate in the Cascades arc, United States - O’Hara, D.; Karlstrom, L. (Frontiers in Earth Science, 2023)
The morphology and distribution of volcanic edifices in volcanic terrains encodes the structure and evolution of underlying magma transport as well as surface processes that shape landforms. How magmatic construction and erosion interact on long timescales to sculpt these landscapes, however, remains poorly resolved. In the Cascades arc, distributed volcanic edifices mirror long-wavelength topography associated with underlying crustal magmatism and define the regional drainage divide. The resulting strong along- and across-arc modern precipitation gradients and extensive glaciation provide a natural laboratory for climate-volcano interactions. Here, we use 1,658 volcanic edifice boundaries to quantify volcano morphology at the arc-scale, and reconstruct primary edifice volumes to create first-order estimations of Cascades erosion throughout the Quaternary. Across-arc asymmetry in eroded volumes, mirroring similarly asymmetric spatial distribution of volcanism, suggests a coupling between magmatism and climate in which construction of topography enhances erosion by orographic precipitation and glaciers on million-year timescales. We demonstrate with a coupled landscape evolution and crustal stress model that mountain building associated with magmatism and subsequent orographically-induced erosion can redistribute surface loads and direct subsequent time-averaged magma ascent. This two-way coupling can thus contribute to Myr-scale spatial migration of volcanism observed in the Cascades and other arcs globally.